Climatic or dietary change? Stable isotope analysis of Neolithic–Bronze Age populations from the Upper Ob and Tobol River basins - Motuzaite Matuzeviciute, Giedre; Kiryushin, Yurii F.; Rakhimzhanova, Saule Zh; Svyatko, Svetlana; Tishkin, Alexey A.; O’Connell, Tamsin C. (The Holocene, 2016)
Dietary changes in the populations inhabiting southwest Siberia and northern Kazakhstan indicate concurrent changes in the economy, at the same time marking the beginnings of East–West interaction across northern Eurasia. The introduction of domestic animal species of Near Eastern origin, such as sheep and goat, dramatically changed the lives of the local population. Past palaeodietary research using stable isotope analysis has mainly focussed on pastoral populations of the Bronze Age period. It is crucial, however, to assess the diets of humans and animals from earlier periods (Neolithic/Chalcolithic) in order to understand the timing and nature of dietary change during the Bronze Age of southwest Siberia and northern Kazakhstan, in particular the possible contribution of environmental change influencing dietary shifts. In this paper, we report the results of stable isotope analysis on 55 human and 45 faunal samples from southwest Siberia (Upper Ob River) and northern Kazakhstan (Tobol River basin), ranging from the Neolithic to the Bronze Age. These data, combined with published human and faunal collagen results from the region as well as new accelerator mass spectrometer (AMS) radiocarbon dating results, indicate little change in animal diet over time, but a notable change in human diet at ca. 2500 cal. BC. The data allow us to determine the time when pastoralism came to the fore, with concomitant economic differences to the local population.